Sustainable Workforce Development: Lessons from EU Industrial Policies for Postwar Ukraine - Khandii, Olena; Zelenko, Olena; Burko, Iaroslav; Bilous, Yana (European Journal of Sustainable Development, 2025)
This article provides a comprehensive analysis of European Union (EU) policies aimed at addressing workforce shortages in the industrial sector, with particular relevance to Ukraine's postwar recovery challenges. The study investigates how demographic shifts, technological advancements, and labor market transformations have shaped workforce development strategies across key EU nations, including Germany, Poland, Italy, France, the Czech Republic, and Hungary. The research highlights successful EU approaches such as dual education systems, vocational training reforms, and lifelong learning initiatives that have effectively bridged skills gaps while promoting social inclusion. Germany's comprehensive strategy combining skilled immigration programs with digital transformation serves as a particularly instructive model, whereas Poland's experience with diaspora reintegration offers valuable insights for Ukraine's displaced populations. The study also examines innovative solutions such as Italy's visa lottery system and France's emphasis on technological upskilling. For Ukraine, which faces acute labor shortages exacerbated by wartime displacement and economic disruption, the article emphasizes the critical need to adapt these European best practices. Key recommendations include establishing sector-specific training programs, developing flexible certification systems for displaced workers, and creating public?private partnerships to align education with industry needs. The analysis particularly stresses the importance of digital skills development and gender-inclusive workforce policies to meet the demands of modern industrial sectors. Methodologically, this study employs comparative policy analysis to identify transferable solutions that could strengthen Ukraine's industrial workforce while supporting broader economic reconstruction efforts. The findings suggest that a strategic combination of EU-inspired vocational education reforms, targeted immigration policies, and technology-driven productivity enhancements could help Ukraine overcome its postwar labor challenges while fostering sustainable economic growth. Keywords: labor shortage, workforce development, industrial sector, EU labor policies, postwar recovery